Biochar alters microbial community and carbon sequestration potential across different soil pH - Sheng, Yaqi; Zhu, Lizhong (The Science of the total environment, 2018)
•CO2 emission from biochar-amended soils with two different pH levels was studied.•Higher biochar degradation resulted in higher CO2 emission in acidic ferralsol.•Biochar increased the bioavailability of SOC and copiotrophic bacteria in ferralsol.•Adsorption of SOC on biochar resulted in decreased CO2 emission in phaeozems. [Display omitted] Biochar application to soil has been proposed for soil carbon sequestration and global warming mitigation. While recent studies have demonstrated that soil pH was a main factor affecting soil microbial community and stability of biochar, little information is available for the microbiome across different soil pH and the subsequently CO2 emission. To investigate soil microbial response and CO2 emission of biochar across different pH levels, comparative incubation studies on CO2 emission, degradation of biochar, and microbial communities in a ferralsol (pH5.19) and a phaeozems (pH7.81) with 4 biochar addition rates (0.5%, 1.0%, 2.0%, 5.0%) were conducted. Biochar induced higher CO2 emission in acidic ferralsol, largely due to the higher biochar degradation, while the more drastic negative priming effect (PE) of SOC resulted in decreased total CO2 emission in alkaline phaeozems. The higher bacteria diversity, especially the enrichment of copiotrophic bacteria such as Bacteroidetes, Gemmatimonadetes, and decrease of oligotrophic bacteria such as Acidobacteria, were responsible for the increased CO2 emission and initial positive PE of SOC in ferralsol, whereas biochar did not change the relative abundances of most bacteria at phylum level in phaeozems. The relative abundances of other bacterial taxa (i.e. Actinobacteria, Anaerolineae) known to degrade aromatic compounds were also elevated in both soils. Soil pH was considered to be the dominant factor to affect CO2 emission by increasing the bioavailability of organic carbon and abundance of copiotrophic bacteria after biochar addition in ferralsol. However, the decreased bioavailability of SOC via adsorption of biochar resulted in higher abundance of oligotrophic bacteria in phaeozems, leading to the decrease in CO2 emission.